PROSES DEKOMPOSISI BATANG KELAPA SAWIT (Elaeis guineensis Jacq.) METODE REPLANTING SISIPAN DAN PENCINCANGAN - Nasamsir, Nasamsir; Defitri, Yuza; Suhermanto, Heri (Jurnal Media Pertanian, 2017)
Â This research was carried out in Panca Mulya Village, Sungai Bahar District, Muaro Jambi Regency, Jambi Province since August to September 2017. The material that used was weathering stems of oil palm that already previously replanting by 6 to 7 months, while the tools that used was the Global Positioning System (GPS) with Garmin GPSmap 78s as its brand, plastic bag, holding tool, camera, and stationery. This research was carried out by survey methods applying. Samples was collected from the replanting areas of both underplanting and chipping method, respectively 2 blocks with 3 locations each block had 200 m distance to North direction with 0.2 kg weight. Secondary data was collected from a company and Indonesian Agency for Meteorological, Climatological and Geophysics (Badan Meteorologi, Klimatologi, dan Geofisika or simply BMKG) while primary data was an interviews with farmers using a questionnaire. The collected data were : general description of research location, rainfall, temperature, humidity, soil acidity, C-N ratio of oil palm stem both before and after decomposition, from the replanting of both underplanting and chipping methods. The result of this study showed that C-N ratio of oil palm stem before decomposition was 58.42, C-N ratio of oil palm stem decomposition that replanting with underplanting method was 37.18, and the average C-N ratio of chipping method was 14.24. Be equaling with the compost quality specifications on Indonesian national Standar (Standar Nasional Indonesia (SNI) 19-7030-2004, so C/N value of decomposition process of oil palm stem that replanting by chipping method was already meet this standard with 10 to 20 as a C/N grade. Keywords ; C-N ratio, oil palm, replanting methodPenelitian ini dilaksanakan di desa Panca Mulya, kecamatan Sungai Bahar, kabupaten Muaro Jambi, Jambi pada bulan Agustus sampai September 2017. Bahan yang digunakan adalah hasil pelapukan batang Kelapa sawit yang sudah direplanting 6 sampai 7 bulan sebelumnya, sedangkan alat-alat yang digunakan adalah Global Positioning System (GPS) merek Garmin GPSmap 78s, kantung plastik, alat pengambil bahan, kamera, dan alat tulis. Penelitian ini dilaksanakan dengan metode survey, sampel dikumpulkan dari areal replanting metode sisipan dan matode pencincangan, masing-masing 2 blok pada 3 titik setiap blok jarak 200 m arah utara dengan berat 0.2 kg. Data sekunder dikumpulkan dari perusahaan atau BMKG dan wawancara dengan petani menggunakan kuisioner. Data yang dikumpulkan adalah ; informasi umum lokasi penelitian, curah hujan, suhu, kelembaban, pH tanah, rasio C-N batang Kelapa sawit sebelum dekomposisi, serta rasio C-N hasil dekomposisi.dari replanting metode sisipan dan pencincangan. Hasil penlitian menunjukkan nisbah C-N batang Kelapa sawit di daerah penelitian sebelum dekomposisi 58,42, rasio C-N dekomposisi batang Kelapa sawit replanting dengan metode sisipan rata-rata 37.18, dan metode pencincangan rata-rata 14,24. Bila disetarakan dengan spesifikasi kualitas kompos SNI 19-7030-2004, nilai C/N proses dekomposisi batang Kelapa sawit hasil replanting metode pencincangan sudah memenuhi standar dengan nilai C/N 10 sampai 20.Kata kunci ; rasio C-N, Kelapa sawit, metode replanting